Peran Strategis Guru PAI dalam Implementasi Living Kurikulum di Sekolah - Nurul Qomariyah; Nia Azizunnisa; Mochammad Iskarim (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
Islamic Religious Education plays a strategic role in shaping the character, faith, and morals of students amidst the challenges of modern development. Therefore, the role of Islamic Religious Education teachers is needed, not only focusing on delivering material but also being able to bring Islamic values ​​to life in learning practices through the application of a living curriculum. This study aims to examine the role of Islamic Religious Education teachers in the implementation of a living curriculum in schools. The research method used is library research by analyzing various relevant literature sources, including books, scientific journals, and supporting documents. The results of the study indicate that Islamic Religious Education teachers play a crucial role as organizers, transformers, facilitators, innovators, and evaluators. As organizers, teachers manage school learning and religious activities to ensure their effectiveness. As transformers, teachers instill Islamic values ​​through role models and contextual learning. The facilitator role is realized by providing a conducive and motivating learning environment for students. Furthermore, as innovators, Islamic Religious Education teachers utilize technology and creative learning approaches that are relevant to current developments. As evaluators, teachers conduct objective and comprehensive assessments of students' cognitive, affective, and psychomotor aspects. In conclusion, the comprehensive role of Islamic Religious Education teachers is crucial to the successful implementation of the living curriculum in developing students who are devout, have noble character, and are adaptable to modern challenges.